PERLINDUNGAN HUKUM TERHADAP PENJUAL DALAM TRANSAKSI JUAL BELI ONLINE DENGAN METODE PEMBAYARAN CASH ON DELIVERY (COD) - Bennedicta, Shelva Shendy; Purwo Sulistyo, Al Qodar (UNES Law Review, 2023)
Buying and selling online is an option that is in great demand by the public because it has many conveniences and advantages. With the increasing sophistication of online buying and selling transactions, there are also many choices of payment methods for these transactions, one of which is Cash On Delivery or what is commonly referred to as (COD). However, along with its development, many sellers have suffered losses from the Cash On Delivery payment method. This paper aims to find out how legal protection is for sellers in online buying and selling transactions with the Cash On Delivery payment method and also what legal remedies can be used by sellers. This paper uses a normative juridical research method by applying a statutory approach, namely by means of an analysis of statutory regulations and provisions in accordance with the problems being handled. The results of this paper explain that legal protection for sellers in carrying out online buying and selling transactions with the Cash on Delivery payment method is contained in Article 6 of Law Number 9 of 1999 concerning Consumer Protection. In addition, to protect the rights of the seller, there are also legal remedies that can be taken, namely by way of settlement out of court through Alternative Dispute Resolution. In this case the settlement of disputes through the courts is expected to be the final effort that will be taken by the seller and the buyer after other methods do not result in an agreement.